The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/2446-4740.00617
|View full text |Cite
|
Sign up to set email alerts
|

Pattern recognition of abscesses and brain tumors through MR spectroscopy: Comparison of experimental conditions and radiological findings

Abstract: Introduction: The interpretation of brain tumors and abscesses MR spectra is complex and subjective. In clinical practice, different experimental conditions such as field strength or echo time (TE) reveal different metabolite information. Our study aims to show in which scenarios magnetic resonance spectroscopy can differentiate among brain tumors, normal tissue and abscesses using classification algorithms. Methods: Pairwise classification between abscesses, brain tumor classes, and healthy subjects tissue sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…The reason could be that this tumour can be difficult to differentiate from other tumours with regard to cellular architecture and molecular patterns, also for the pathologist [ 17 , 18 ]. A recent study using cases from the INTERPRET database showed that even for the binary classification of anaplastic astrocytoma compared to other tumour grades or healthy tissue, an area under curve > 0.9 in receiver operating characteristics operating analysis was infrequently achieved at 1.5 T with a short TE [ 19 ]. In an earlier study on the other hand, the use of INTERPRET was better than MRI for characterisation of anaplastic astrocytoma [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reason could be that this tumour can be difficult to differentiate from other tumours with regard to cellular architecture and molecular patterns, also for the pathologist [ 17 , 18 ]. A recent study using cases from the INTERPRET database showed that even for the binary classification of anaplastic astrocytoma compared to other tumour grades or healthy tissue, an area under curve > 0.9 in receiver operating characteristics operating analysis was infrequently achieved at 1.5 T with a short TE [ 19 ]. In an earlier study on the other hand, the use of INTERPRET was better than MRI for characterisation of anaplastic astrocytoma [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to diagnosis, the need for multicentre studies seems well established since the INTERPRET experience on preoperative brain tumour typing/grading at 1.5 T . The fact that the curated INTERPRET dataset has been made accessible to research groups allows them to develop classifiers comparing single‐centre cohorts with that dataset, for example to differentiate abscesses from tumours at 3 T . Diagnosis of paediatric brain tumours has also been the subject of two recent works at 1.5 T on a large cohort of 90 patients and at 3 T in a multicentre study on 41 patients, to distinguish among the three main paediatric brain tumours (medulloblastoma versus pilocytic astrocytoma versus ependymoma).…”
Section: Mrs Cancer Patternmentioning
confidence: 99%
“…The problem of imbalanced classes has also been tackled with the use of AdaBoost . Supervised pattern recognition techniques such as support vector machines, linear discriminant analysis or several different algorithms, and classifier fusion, are also used in the latest literature, mainly for diagnostic questions. These methodologies are, generally too sophisticated to be put in practice by purely clinical groups, and when methodologies are tested the norm is availability of very small datasets, although there are exceptions such as Reference 113 or 109.…”
Section: Mrs Cancer Patternmentioning
confidence: 99%
“…The reason for this scarcity may be the difficulty in examining and interpreting MRS signals. Therefore, artificial intelligence and computer-aided diagnosis (CAD) are novel and effective methods that can contribute to overcoming the problems mentioned above 16,17,18 . To the best of our knowledge, very few studies have addressed the determination of MS types with the help of combined approaches, adopting both MRS and advanced machine learning algorithms.…”
Section: Introductionmentioning
confidence: 99%